PERANCANGAN APLIKASI GAME PEMBELAJARAN OPERASI PERHITUNGAN MATEMATIKA KELAS 3 SD MENGGUNAKAN UNITY - Kristina Kristina; Talitha Talitha (INTEKSIS, 2021)
Math games are educational games that contain a collection of math questions that aim to learn math in a fun way. This paper has the title "Designing Applications for Learning Operations Mathematics Operations for 3rd Grade Children Using Unity". This paper shows a report on the results of a math game called "Math Quiz". The purpose of this paper is to show a math quiz game made using unity. Math quiz game is made using unity 3D. Unity is an application for creating or developing games for both beginners and professionals. Unity can create 2D and 3D games, as needed. This math quiz game is made in 2D. Unity is very suitable for use by beginners because it has a simple interface and Unity is easy to learn for beginners. The result of the math quiz game made using Unity 3D is that it has a simple interface, has a few features that still need development so that the features are more and better, and games are made suitable for elementary school children. Keywords: Game, Mathematics, Unity 3D, Elementary School